If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5)(8x + -3) = 0 Reorder the terms: 3(5 + x)(8x + -3) = 0 Reorder the terms: 3(5 + x)(-3 + 8x) = 0 Multiply (5 + x) * (-3 + 8x) 3(5(-3 + 8x) + x(-3 + 8x)) = 0 3((-3 * 5 + 8x * 5) + x(-3 + 8x)) = 0 3((-15 + 40x) + x(-3 + 8x)) = 0 3(-15 + 40x + (-3 * x + 8x * x)) = 0 3(-15 + 40x + (-3x + 8x2)) = 0 Combine like terms: 40x + -3x = 37x 3(-15 + 37x + 8x2) = 0 (-15 * 3 + 37x * 3 + 8x2 * 3) = 0 (-45 + 111x + 24x2) = 0 Solving -45 + 111x + 24x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-15 + 37x + 8x2) = 0 Factor a trinomial. 3((-5 + -1x)(3 + -8x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-5 + -1x)' equal to zero and attempt to solve: Simplifying -5 + -1x = 0 Solving -5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 0 + 5 -1x = 0 + 5 Combine like terms: 0 + 5 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5Subproblem 2
Set the factor '(3 + -8x)' equal to zero and attempt to solve: Simplifying 3 + -8x = 0 Solving 3 + -8x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -8x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -8x = 0 + -3 -8x = 0 + -3 Combine like terms: 0 + -3 = -3 -8x = -3 Divide each side by '-8'. x = 0.375 Simplifying x = 0.375Solution
x = {-5, 0.375}
| 52=4y | | 4x+12=7x-15 | | 3(2y-7)=12 | | 8x+4=6x+5 | | 4x^4-53x^2+49=0 | | (3x-2)(3x-2)=16x^2 | | 145=x+x+1 | | 125c^3-1= | | -.3a+1.4=-1.2-.7a | | 11=-4r | | -11=-4r | | 5(y+2)=25 | | -11r=-4r | | -67=4x+3-7x | | 10.2x+95.31=-9.8x+95.07 | | y=x^2-5x-50 | | 14-3x=-2x+5 | | (3x-1)(x+7)=0 | | 4(x+1)=2x+12 | | 2y-1=-7 | | 4x-10=56 | | 7.5x-2.8=4.7 | | 354=x+x+4 | | 2x^2+19x+42= | | 8x^9y^3+1000= | | 3x^2+6x+5=0 | | 7x+3=2x+28 | | 0.2[x+2]+2x=6x-10 | | 4b+7b-1.6=1.2 | | 6d^2+21b=10d+35 | | (3x-2)2=16x^2 | | 2(0)+7y=5 |